How did David prepare to talk to Goliath? : South Africa's experience of trade negotiations with the EU - Bilal, Sanoussi (European Centre for Development Policy Management MaastrichtNL, 2004)
Reviews the way South Africa organised itself to prepare for and conduct the negotiations on the Trade, Development and Cooperation Agreement with the EU. Outlines some difficulties South Africa encountered in the preparation and dimensions in the negotiating process that could have received greater attention. Offers general insights and lessons on how developing countries can effectively prepare for and conduct trade negotiations.